Odpowiedź:
Szczegółowe wyjaśnienie:
A. 2x+6y + (-10x) -15y-x-y =2x+6y-10x-16y-x= -11x -10y
B. 12a² - 6a+ a²-7a-a+ (-14a²)=13a²-12a-14a²= -a²-12a
C. 5x²y + 2xy-7xy² + (-16x²y) - xy +y²x=5x²y+2xy-6xy²-16x²y=5x²y -22xy²+2xy
D. 1,2ab − b + a − 1/3ba + 7/9b - 3/7a+ (-ab)=1,2ab-ab-1/3ab-2/9b+4/7a=2/5ab-1/3ab-2/9b+4/7a=6/15ab-5/15ab+4/7a-2/9b=1/15ab+4/7a-2/9b
E. 4 1/4xar-arx+ 1/2ar-xr-3 1/4rax + 1,5ra + xr=1/2ar+1,5ar=0,5ar+1,5ar=2ar
F. 4.2km - 0.2mm + 4mk-10k +12km -0,8m² + 21k=20,2km-m²-10k
G. 3ws²z + 4wsz- 2sz² + (-3/4s² wz) + wsz - 7z²s=3s²wz-3/4s²wz+5swz-5sz²=2 1/4s²wz+5swz-5sz²